Strategic Roadmap for Biodiesel Market Leadership Using Analyze-Formulate-Implement Framework and Analytical Hierarchy Process in Indonesia - Ida Rosida; Gallang Perdhana Dalimunthe; Widhyawan Prawiraatmadja (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Indonesia’s biodiesel industry, driven by government mandates like the 2025 biodiesel blending policy, relies heavily on imported sodium methylate oxide, exposing it to supply chain risks and cost fluctuations. This study aims to develop a strategic roadmap for Company to enhance its market position in the sodium methylate oxide market and achieve a 50% market share by 2029. Employing the Analysis-Formulation-Implementation Framework, the research integrates qualitative interviews with stakeholders and quantitative analysis using the Analytic Hierarchy Process. Findings reveal that price, supply reliability, and product quality are critical factors influencing biodiesel producers’ purchasing decisions. The Analytic Hierarchy Process prioritizes financial (29.9%), operational (27.9%), strategic (24.7%), and risk (17.5%) criteria, with the Borrow strategy forming partnerships with existing producers identified as the most effective approach (39.1%). The implementation plan focuses on strategic partnerships in key regions, starting with partner selection in 2025 and commercialization by 2028. This strategy leverages Company’s strengths to reduce import dependency and enhance competitiveness. The study concludes that this approach positions Company as a market leader, supporting Indonesia’s renewable energy goals while offering a replicable framework for strategic decision-making in the petrochemical sector.